A No Alarm on ECG: A Case of Severe Asymptomatic Hyperkalemia with No Significant ECG Changes - Namrah Nasir, Namrah; Nabi, Zahid; Rashid, Humayun (Pakistan Journal of Kidney Diseases, 2025)
Hyperkalemia usually produces characteristic ECG changes due to its effects on myocardial membrane potential. When these accompany high serum potassium levels, they indicate a medical emergency. However, ECG findings do not always correlate with biochemical severity—sometimes even profound hyperkalemia presents with a normal ECG. We present a case of a 47-year-old woman with chronic kidney disease who exhibited a serum potassium level of over 8 mmol/L yet remained asymptomatic with a normal ECG. This case highlights the diagnostic limitations of ECG in hyperkalemia and emphasizes that management should be guided by biochemical results and clinical context rather than ECG appearance alone.